Work rate adjustments needed to maintain heart rate and RPE during high-intensity interval training in the heat - Yoder, H. A.; Mulholland, A. M.; MacDonald, H. V.; Wingo, J. E. (Frontiers in Physiology, 2025)
Introduction: Higher work rates may be sustainable when maintaining target rating of perceived exertion (RPE) compared to maintaining target heart rate (THR) during high-intensity interval training (HIIT) exercise in hot conditions, but may also result in greater thermal strain and cardiovascular drift, as well as greater decrements in maximal oxygen uptake (VO2max).